Evangelical dictionary of world missions - Moreau, A. Scott; Netland, Harold A.; Engen, Charles Edward van; Burnett, David (Baker reference library, 2000)
With more than 1,400 articles on mission theory and practice, theology, and history, this comprehensive resource presents a wealth of information on the topic of world missions. The Evangelical Dictionary of World Missions includes contributions by over three hundred missionaries, theologians, and educators from a variety of cultural, denominational, and ethnic backgrounds. The contributors write from an evangelical perspective, but they are concerned to provide a broad international and interdenominational survey of the history of world missions as well as current trends and research.